FAKTOR YANG MEMPENGARUHI PERILAKU KESEHATAN PADA MASYARAKAT KELURAHAN HALIM PERDANAKUSUMA DALAM UPAYA PENCEGAHAN COVID-19 MELALUI MODEL INFORMATION MOTIVATION AND BEHAVIORAL SKILLS - Tasha Anindya Syafa (2022)
For more than a year, Indonesia has experienced the COVID-19 pandemic. However, there are still weaknesses in the implementation of health behavior, especially in DKI Jakarta. Whereas health behavior is needed as an effort to prevent COVID-19 in the face of the 'Public Health Emergency of International Concern' alarmed by World Health Organization. This study aims to determine factors that influence health behavior in the ward of Halim Perdanakusuma in efforts to prevent COVID-19 through Information Motivation And Behavioral Skills Model. This study used cross-sectional approach, with 158 total of samples located in the ward of Halim Perdanakusuma. Samples were taken through a two-stage sampling method. The first stage is the cluster random sampling and followed by stratified random sampling. Furthermore, the data results were analyzed using univariate, bivariate (chi-square test with CI 95%) and multivariate (logistic regression) analysis. Motivation (p-value = 0,001) and behavioral skill (p-value = 0,000) had significant direct effect on health behavior in efforts to prevent COVID-19 whilst education level and information of COVID-19 (p-value > 0,05) had no significant direct effect on health behavior in efforts to prevent COVID-19. The best predictor factor of health behavior in efforts to prevent COVID-19 is behavioral skills. Where people with high behavior skills are more likely to carry out good health behavior in efforts to prevent COVID-19 (OR = 6,643). In dealing with public health emergency due to the COVID-19 pandemic that happened in Indonesia, the government should focus on improving health education and promotion on behavioral skills.